Sitting on the fence – Spain’s delicate balance: bordering, multiscalar challenges, and crimmigration - Wonders, Nancy A. (European journal of criminology, 2017)
In a widely circulated image from the Spanish enclave of Melilla, over 20 young men sit perched atop a razor-crowned border fence that is emblematic of the sharp divide between bare life in poor nations and a life of relative privilege in the West. Metaphorically, Spain, too, sits on a fence: Spain struggles to balance its history as a sovereign nation that experienced rapid economic growth, in part by incorporating migrants into the labour force, with contemporary pressures to fortify external and internal borders. This article analyses the way that contemporary crimmigration policy developments in Spain both reflect and help to produce the complex multiscalar dynamics that the nation must delicately balance in response to the challenges posed by Europeanization, economic crisis, and influences from below.